Enlightened City: A Society Built on the Prophetic Motivational Model - Farid, Farnaz (Al-Amīr Research Journal for Islamic Studies, 2024)
This paper discusses the motivations that worked to build an exemplary society of all time: the Enlightened City – Medina Al Munawarah. It sheds light on the Prophet’s motivational strategies and leadership skills to establish youth in society. It examined how the Prophet built a society based on empathy and mercy for people of all ages, races, and colours. It defines a new Motivational model called the “Prophetic Motivational Model” and builds on it to show how it can be employed in today’s time to create a harmonious community and a larger society. Key Words: Prophetic Motivational Model, Enlightened City, Medina Al Munawarah, Prophet Muhammad ﷺ, community harmony, youth-development, inclusive society, Islamic leadership.